PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), NET PROFIT MARGIN (NPM) DAN NET INTEREST MARGIN (NIM) TERHADAP HARGA SAHAM PT BANK SYARIAH INDONESIA TBK TAHUN 2019-2023. - Sari Akbar, Efi Ratna; Rizqi, Reza Muhammad (Publika Citra Media, 2025)
This study aims to analyze the effect of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Net Profit Margin (NPM), and Net Interest Margin (NIM) on the stock price of Islamic banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2021-2023. The financial performance of a company, especially in the Islamic banking sector, is an important factor that can influence investors' decisions in investing in the capital market. This study uses secondary data obtained from the annual financial reports of Islamic banking companies listed on the IDX. The analysis method used is multiple linear regression with the classical assumption test to ensure the validity of the research model. The results of the study show that the variables ROE, EPS, NPM, and NIM have a positive and significant effect on stock prices, while ROA does not have a significant effect. This finding indicates that investors consider the factors of return on equity, earnings per share, net profit margin, and net interest margin more in assessing the price of Islamic banking stocks compared to return on assets. The results of this study are expected to be a reference for investors in making investment decisions and for Islamic banking companies in improving financial strategies to increase the value of their shares in the capital market.